The formation of fractal carbon structures in the plasma ARC discharge - L. G. Keush (Хімія, фізика та технологія поверхні)
Fractal structures are common in nature, and the structures that play a role in the formation of macroscopic systems, as well as represent new structures characterized by dramatic changes in the physical properties. The aim of this work is to determine the dimensions of fractal carbon structures using electron microscopy and provision characteristics of fractal carbon structures by calculating the fractal dimension. The feedstock for fractal structures in an arc discharge is a mixture of pyrolytic carbon and coal tar. The fractal carbon structures has been systematically studied by scanning electron microscopy (SEM) and transmission electron microscopy. The SEM observation shows quite a large range of sizes of fractal clusters and aggregates. The TEM analysis reveals formation of carbon nanoparticles in a narrow range of 2–8 nm. The results show that the fractal structure of the carbon deposits are volumetric fractals with dimension of carbon deposits of 2.96. Volume fractal structure consisting of fractal aggregates, the cloud formations, and the like ones having a similar structure may be formed of different materials - graphite and pyrolytic carbon. A necessary condition for the nucleation of carbon nanostructures is the formation of carbon nanoparticles in an arc discharge.